Perubahan kimia dan sensoris buah salak pondoh selama penyimpanan dalam termodifikasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Salak pondoh (Salacca edulis RENW cultivar Pondoh) is an exotic fruit of Indonesia which is prospective as an export commodity. However, the problem is that the fruit has a short shelf life. The purpose of the investigation was to prolong the shelf life of the produce by storing them in a modified atmosphere (MA). The composition of MA was 02, 1-3%